2010
DOI: 10.3329/jsr.v2i3.4667
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Metals in Frozen and Canned Marine Fish of Korea

Abstract: Heavy metal contaminants in fish are of particular interest because of the potential risk to humans who consume them. The edible muscles of eight different species of fishes were analyzed by ICP-MS (Inductively Coupled Plasma Mass Spectroscopy) for heavy metals, collected from Market in Gwangju, Korea during April-May in 2008. The concentrations of Hg, As, Cd, Cr, Cu, Fe, Mn, Ni, Pb and Zn varied between 0.24±0.007 - 0.01±0.001, 44.54±5.69 - 1.23±0.20, 0.13±0.05 – ND (not detected), 1.32±0.47 - 0.09± 0.02, 3.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 9 publications
2
11
3
Order By: Relevance
“…In another study, Hussein and Khaled (2014) reported that the mean concentrations of Cr in muscle of three tuna species from Alexandria, Egypt were 0.82 ± 0.07 µg/g w.wt. Also, Islam, Bang, Kim, Ahmed, & Jannat, (2010) reported that the mean concentration of Cr (µg/g, DW) in canned longtail tuna which was imported from the USA, canned bluefin tuna which was imported from the Thailand and canned bluefin tuna (produced in Korea) were 0.58 ± 0.06, 0.32 ± 0.002 and 0.25 ± 0.02, respectively and similar to this study lower than MPL (Islam et al, 2010). A comparison of the Cr concentrations in the canned fish samples marketed in Iran and other selected regions are presented in Table 3.…”
Section: Discussionsupporting
confidence: 58%
“…In another study, Hussein and Khaled (2014) reported that the mean concentrations of Cr in muscle of three tuna species from Alexandria, Egypt were 0.82 ± 0.07 µg/g w.wt. Also, Islam, Bang, Kim, Ahmed, & Jannat, (2010) reported that the mean concentration of Cr (µg/g, DW) in canned longtail tuna which was imported from the USA, canned bluefin tuna which was imported from the Thailand and canned bluefin tuna (produced in Korea) were 0.58 ± 0.06, 0.32 ± 0.002 and 0.25 ± 0.02, respectively and similar to this study lower than MPL (Islam et al, 2010). A comparison of the Cr concentrations in the canned fish samples marketed in Iran and other selected regions are presented in Table 3.…”
Section: Discussionsupporting
confidence: 58%
“…Lead damages and destroys erythrocytes; reduces resistance; weakens the bones; blocks the nervous system; inhibits the absorption of iodine, necessary for correct functioning of the thyroid gland; forms toxic deposits in the organism, causing numerous disorders and diseases, [41]; 0.053-0.7396, 0.0195-0.0489 [18]; 0.07-0.22 [72]; <LOQ-1.14 [17]; 0.0001-0.0003 [52]; 0.0378-0.5243 [73]; 0.60-0.62 [74]; 0.088-0.410, [43]; 0.005-1.17 [39], * 0.140-0.327 in d.w. [75], * 0.094-0.466 [76], * 0.16-0.53 [77] 0.50 and 1.0 (tuna) [26] As Cd 0.0033-0.0754 0.0046-0.0720 [16]; 0.002-0.07 [78]; 1.00-1.80 [66]; 0.08-0.66 [41]; 0.0-53.9 [18]; 0.019 [79]; <LOQ-0.09 [17]; 0.08 [36]; 0.0032-0.0834 [73]; 0.020-0.025 [74]; <LOQ-0.007 [39]; 0.03-0.12 [37]; <LOQ-0.18 [40]; 0.19-17.05 [80], * 0.008-0.191 in d.w. [75], * 0.021-0.082 [76], * 0.01-0.21 [77] 0.050 and 0.10 (sardine, tuna) [26] Pb 0.011-0.296 0.0126-0.0726 [16]; 0.007-0.51 [78]; 3-4.60, 3.60-4.00 [66]; 0.14-0.92 [41]; 0.02-1.37 [35]; 0.0-31.1 [18]; 0.11 [79]; <LOQ-4.13 [17]; 0.10 [36]; <LOQ-3.19, 0.35-2.10, 0.25-1.51 in d.w. [42]…”
Section: Comparison With Reported Literature Values and Withmentioning
confidence: 99%
“…The fish caught off the Coast of Langkawi Island in Malaysia. Results showed that, all fish species had higher concentrations of Zn compared to other elements, (Pb) and (Hg) were found to have lower concentration Islam et al (2010). observed heavy metal contaminants in fish, which are of particular interest because of the potential risk to humans who consume them.…”
mentioning
confidence: 93%